MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KONEKSI MATEMATIS SISWA SMA DALAM PEMBELAJARAN DARING DENGAN MODEL ADVANCE ORGANIZER - Masta Hutajulu; Ika Wahyu Anita (IKIP Siliwangi, 2021)
This study aims to measure the achievement and improvement of problem solving abilities and mathematical connections of high school students in online learning using an advance organizer model. This study used a quasi-experimental approach, and data analysis used a two-way annova for knowing improvement of problem solving abilities and mathematical connections on low, medium, and high student level.. Research conducted at high school have the conclusion that there is a significant difference between students with the Advance Organier model and students who use regular learning seen from the high, medium and low level students.